USE OF EDUCATIONAL AND COGNITIVE TASKS AIMED ON THE FORMATION OF INTELLECTUAL STUDENTS' SKILLS (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the principal features of a cognitive assignments system. Its influence on formation students' intelligence skills has been revealed.
Keywords: cognitive task; intellectual skills; intellectual activity